Family climate and aggressiveness between high school students from Metropolitan Lima - Matalinares Calvet, María (2010)
The present research work started with an objective of establish if it existed or not relation between family climate and aggressiveness in students of 4th and 5th of high school from Metropolitan Lima. The sample comprised 237 students of 4th and 5th of high school level, of both sexes, with aged between 14 and 18 years, from different educational state centers of Lima to whom were applied the Hostility Inventory of Buss-Durkee, proposed for A. H. Buss and A. Durkee in 1957, adapted for Peru by Carlos Reyes R. in 1987 and the Family Environment Scale (FES) by R.H. Moos, B.S. Moos and E.J. Trickett whose standardization was realized by Cesar Ruiz. The results indicate that the variables family climate and aggressiveness are correlated. Besides, the results about different subtests of the Family Environment Scale show a correlation between the dimension Relation of Family Environment Scale with the subscales Hostility and Verbal Aggressiveness. There was not a relation between the dimension Development of the Family Environment Scale and the subscales of the Hostility Inventory. There was significant differences on genre in high school students about Family Environment Scale, particularly in the dimension Stability between males and females. The aggressiveness of the students also show significant differences on the genre in the subscale of physical aggressiveness between males and females.